종아리근 단축 대상자에게 목말뼈 후방활주 테이핑을 이용한 관절가동술 적용과 근막이완기법의 적용이 동적 균형의 운동학적 변화에 미치는 영향 - 서민아; Min-a Seo; 정규나; Kyu-Na Jeong; 김유진; Yu-jin Kim; 이유진; Yu-jin Lee; 황영인; Young-in Hwang (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2022)
Background: Individuals with calf muscle shortening may have decreased dynamic balance. Objects: This study aimed to investigate the effect of mobilization with movement (MWM) and myofascial release (MFR) on kinematic changes in dynamic balance in individuals with calf muscle shortening. Methods: Thirteen participants were randomly assigned to the MWM or the mobilization with movement added myofascial release (MWM-MFR) group. The MWM group received treatment with only MWM, whereas the MWM-MFR group was treated with MWM and MFR. Pre- and post-intervention passive range of motion (PROM), maximum reaching lengths, and modified star excursion balance test (MSEBT) results were compared for all participants. Wilcoxon signed-rank test and Mann-Whitney U test were used for statistical analysis. Results: The results showed significant within-group differences in ankle PROM, but no significant between-group differences. The maximum reaching length in the MWM-MFR group in the posterolateral direction was significantly different before and after the intervention (p = 0.005). This group also showed significantly reduced ankle abduction in MSEBT during the posteromedial direction section 3 (p = 0.007) and posterolateral direction section 5 (p = 0.049) compared with the MWM group. Conclusion: Combined MWM and MFR intervention improves ankle stability in the coronal plane during the posteromedial and posterolateral forward movement in dynamic balance compared with only MWM in individuals with calf shortening.